Automatic Artifact Detection Algorithm in Fetal MRI - Lim, Adam; Lo, Justin; Wagner, Matthias W.; Ertl-Wagner, Birgit; Sussman, Dafna (Frontiers in Artificial Intelligence, 2022)
Fetal MR imaging is subject to artifacts including motion, chemical shift, and radiofrequency artifacts. Currently, such artifacts are detected by the MRI operator, a process which is subjective, time consuming, and prone to errors. We propose a novel algorithm, RISE-Net, that can consistently, automatically, and objectively detect artifacts in 3D fetal MRI. It makes use of a CNN ensemble approach where the first CNN aims to identify and classify any artifacts in the image, and the second CNN determines the severity of the detected artifacts. The main mechanism in RISE-Net is the stacked Residual, Inception, Squeeze and Excitation (RISE) blocks. This classification network achieved an accuracy of 90.34% and a F1 score of 90.39% and outperformed other state-of-the-art architectures, such as VGG-16, Inception, and ResNet-50. The regression network across all classes had an MSE of 0.083. The presented algorithm facilitates rapid and accurate fetal MRI quality assurance.